Densidades urbanas e o concurso Bairro Novo - Ramos, Ricardo Carvalho Lima (2010)
This dissertation contains an analysis of the urban density proposals of ten projects that were awarded in the Bairro Novo Contest, held in 2004. To do this, an investigation is made, starting with the industrial revolution, of historical antecedents which left a mark on 18th, 19th and 20th century cities in the form of designs and plans.